What Constitutes Evidence of Discrimination in Lending? - Ferguson, Michael F.; Peters, Stephen R. (Journal of Finance, 1995)
We analyze a simple model of bank lending in order to ascertain what can be inferred from relative denial and default rates about lending discrimination. We show that if minority applicants are of lower average creditworthiness than majority applicants, then, contrary to a popular argument, a uniform, nondiscriminatory credit policy cannot simultaneously produce (i) higher denial rates for minority applicants, and (ii) equal default rates for minority and majority applicants. Moreover, we show that equality of denial or default rates always implies discrimination. In particular, equal denial (default) rates imply discrimination against majority (minority) applicants.